METHODOLOGY FOR USING DESIGN TECHNOLOGIES IN TEACHING EDUCATION - Makulov Shukhrat Kholmatjonovich (The Conference Hub, 2025)
This article analyzes technologies for teaching future educators to design methodology in teaching educational science. The article examines the role of design methodology in the educational system and how it affects the personal, moral, and social development of students. The application of design methodology in the teaching process of educational science serves as an effective tool in the development of independent thinking and creative approaches of students. The article provides a detailed analysis of the importance of modern educational technologies used to educate educators on this methodology — Project Education, problem education, interactive methods and blended learning technologies. Also, in the development of methodological skills of future educators, the application of these technologies and its positive impact on the educational system are shown.
Keywords: educational science, design methodology, future educators, educational technologies, methodological qualifications, Project Education, problem education, interactive methods, blended learning, learners, personal development, creative thinking, independent thinking, educational process, pedagogical methods, educational effectiveness.